A MANIPULAÇÃO DA PROLE DURANTE O PERÍODO LACTACIONAL MODIFICA A MORFOFISIOLOGIA MATERNA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2014)
The excess of adipose tissue associated to pathological states, characterizes obesity and overweight. Recent studies have pointed out that the obesity might originate from hormonal and/or neural changes occurred in critical periods of development. Lactation is considered an important developmental window; nutritional changes in this phase might program the offspring metabolism to determine the installation of obesity in adult life. Within this context, few studies have explored the mother adjustments to the offspring changes. Objective: The objective of this present study was to investigate the mother’s morpho-physiological adaptations promoted by the offspring obesity induced in the lactation period. Methodology: Mothers of two kinds of obesity obtained during lactation were studied. In the hyper-nutrition model of lactation the number of offsprings was manipulated 3 days after birth forming a reduced-litter (NR, 3 offsprings) and normal-litter (NN, 9 offsprings). In the hypothalamic obesity model the offsprings received monosodium glutamate (MSG, 4g/Kg) or saline (CON, control) from the 2nd day after birth for five consecutive days. Thus, 4 groups of mothers were evaluated: Mothers-NR x Mothers-NN;Mothers-MSG x Mothers-CON. All groups had body weight and food intake monitored throughout the lactation period. The litter weight was also evaluated during this period. On the 21st day of lactation, after weaning, the rats were anesthetized and received a dose of oxytocin (5U/I) to stimulate milk ejection. Then the milk was collected and aliquots used for the analysis of composition by the creamatocrit and proteins. Next, the rats were sacrificed and the blood collected for biochemical analysis and the fat deposits were extracted and weighed. Mammal tissue samples, white adipose tissue (WAT), brown adipose tissue (BAT) and pancreas were all submitted to histological procedures, dyed with H&E and analyzed through microscopy. The milk leukocytes content was also evaluated through the histological technique. Data were expressed as mean ± standard error of the mean (sem) and evaluated through the Student t test (p<0,05). Results and Discussion: Mothers-NR presented about 36% reduction in the consumption of food and water. 10% reduction in food intake, without changes in water consumption was observed with the Mothers-MSG. There was no alteration of body weight. However, Mothers-NR and Mothers-MSG presented increase of about 56% and 40%, respectively, in ovary fat content. These changes were followed by retroperitoneal fat adipose hypertrophy, (Mothers-NR 67%, Mothers-MSG 22%). The Mothers-NR presented ovary fat hypertrophy (30%), also presented 28% increase in the number of BAT adipose. Biochemical measurements of plasma revealed that both groups presented increase in glucose (Mothers-NR 33%, Mothers-MSG 35%) triglycerides (Mothers-NR 43%, Mothers-MSG 73%) and insulin (Mothers-NR 46%, Mothers-MSG 69%) when compared to the control groups. However, only the Mothers-NR presented changes followed by increase in the milk calories (32%) and fat content (44%). The Mothers-MSG’s milk presented only increase in the amount of leukocytes (54%). The mammal gland in both groups presented increase in adipose content (Mothers-NR 1215%, Mothers-MSG 41%). Morphological changes were also observed in the endocrine pancreas of both groups. Mothers-MSG’s pancreatic islets presented hypertrophy (69%), while the Mothers-NR’s pancreatic islets presented hypotrophy (24%) in relation to the control groups. Morpho-physiological adjustments observed in this data are probably related to the lower energy demand, promoted by the reduction in the number of offsprings, in the case of Mothers-NR and due to changes of suction provoked in the MSG offsprings by the hypothalamic lesion induced by MSG. Conclusion: Data analysis shows that the offspring manipulation promoted the following mother adaptations: i) increase in body fat content and changes in the lipid profile and mother plasma carbohydrates. ii) changes in the milk composition, with increase in the caloric content. These changes were followed by alteration of the mammal gland morphology. iii) changes in the endocrine pancreas histo-morphology, increasing insulin circulating levels.
Keywords: programação metabólica; mães; obesidade; lactação; metabolic programming; mothers; obesity; lactation; CNPQ::CIENCIAS BIOLOGICAS::BIOFISICA::BIOFISICA MOLECULAR